Women and Accidents: The Need to Separate Gender Database. (2016) - Rios, Fernanda Cruz; Chong, Wai K.; Grau, David
Abstract: As female's participation in the US labor force continues to grow, there is a need to separate workplace injuries suffered by men and women. Statistics showed that women faced different types of injuries compared to men, especially on workplace violence. For example, women faced more fatality from workplace violence, and murders by personal acquaintances than men. The authors' study shows that women faced different types of workplace hazards and the risks have been increasing over the past years. Some analysis suggests that some jobs better protect women and the others. The study also finds that there is a lack of understanding of the different safety issues each gender faces, and the lack of data or separation of data between genders. This paper focuses on the main events of fatal and nonfatal injuries among women in all industries, especially on homicides and assaults to shed lights on the gender gaps on safety issues and the need for more gender-specific research and data.